The biomechanics of cartilage: a overview - Eschweiler, Jörg; Horn, Nils; Rath, Bjoern; Betsch, Marcel; Baroncini, Alice; Tingart, Markus; Migliorini, Filippo (Life, 2021)
Articular cartilage (AC) sheathes joint surfaces and minimizes friction in diarthrosis. The resident cell population, chondrocytes, are surrounded by an extracellular matrix and a multitude of proteins, which bestow their unique characteristics. AC is characterized by a zonal composition (superficial (tangential) zone, middle (transitional) zone, deep zone, calcified zone) with different mechanical properties. An overview is given about different testing (load tests) methods as well as different modeling approaches. The widely accepted biomechanical test methods, e.g., the indentation analysis, are summarized and discussed. A description of the biphasic theory is also shown. This is required to understand how interstitial water contributes toward the viscoelastic behavior of AC. Furthermore, a short introduction to a more complex model is given.